Development of e-Books as Teaching Materials for Pteridophyta Material to Improve Students Concept Mastery - Kurniawati, Kurniawati (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The development of science and technology increasingly encourages renewal efforts in the learning process. Research on developing e-books as teaching materials for pteridophyta materials aims to develop e-books as teaching materials for Pteridophyta materials and to improve students' mastery of concepts. The method used is research and development (R&D) with ADDIE design (Analyze, Design, Development, Implementation, Evaluation). The research was conducted from January to July 2020. The population and sample in this study were 36 students of MAN 1 Bogor Regency class X IPA 3 academic year 2019/2020. The implementation of field trials was limited to the cba test with aresearch one-group pretest-posttestdesign. The results showed that: 1) The results of the validation of the feasibility of teaching materials by two experts showed valid criteria without revision with an achievement level of 89% from media experts and v96% from material experts. 2) The developed teaching materials can improve the students' mastery of concepts with an average N-gain value of 0.8 (high). 3) The developed teaching materials received a very good response from teachers and students, with the achievements developed received a very good response from teachers and students with the value obtained from the teacher's response of 87% and from student responses of 90%. Keywords: Concept Mastery, E- book, Pteridophyta